2021
DOI: 10.1007/s11032-021-01249-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a major and stable QTL on chromosome 5A confers spike length in wheat (Triticum aestivum L.)

Abstract: Spike length (SL) is the key determinant of plant architecture and yield potential. In this study, 193 recombinant inbred lines (RILs) derived from a cross between 13F10 and Chuanmai 42 (CM42) were evaluated for spike length in six environments. Sixty RILs consisting of 30 high and 30 low SLs were genotyped using the bulked segregant analysis exome sequencing (BSE-Seq) analysis for preliminary quantitative trait locus (QTL) mapping. A 6.69 12 Mb) region on chromosome 5AL was found to have a signi cant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Under the drought treatment conditions, TGW, GW, and SL were reduced by 4, 2, and 6% compared to the normal conditions ( Figure 1 and Table 1 ). However, the broad sense heritability of TGW, GL, GW, and SL was relatively high (76.16 – 95.66%) under both conditions, consistent with previous studies ( Sukumaran et al., 2018 ; Wolde et al., 2019 ; Ji et al., 2021 ; Wang et al., 2021 ; Wang et al., 2022 ). Furthermore, the association panel showed significant phenotypic variation in TGW, GL, GW, and SL under normal and drought conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Under the drought treatment conditions, TGW, GW, and SL were reduced by 4, 2, and 6% compared to the normal conditions ( Figure 1 and Table 1 ). However, the broad sense heritability of TGW, GL, GW, and SL was relatively high (76.16 – 95.66%) under both conditions, consistent with previous studies ( Sukumaran et al., 2018 ; Wolde et al., 2019 ; Ji et al., 2021 ; Wang et al., 2021 ; Wang et al., 2022 ). Furthermore, the association panel showed significant phenotypic variation in TGW, GL, GW, and SL under normal and drought conditions.…”
Section: Discussionsupporting
confidence: 91%
“…To identify whether QSd.sau-AM-5A.2 is co-located with QTL or genes for SNS or SL reported previously, based on the comparison of QTL for SNS on chromosome 5A with previous studies ( Mo et al, 2021 ), we reviewed the recently published articles related to SL and SNS ( Supplementary Table 8 ). Results showed that many SL or SNS related loci located on chromosome 5AL, but most of the reported QTL or genes were at least tens of Mb away from QSd.sau-AM-5A.2 detected in this study, such as QSl.cib-5A (516.60–521.27 Mb; Ji et al, 2021 ), QTgw.cau.5A_140-142 (698.00–705.40 Mb) and QSsi.cau.5A_91 (586.61–589.22 Mb; Wang et al, 2021 ), QSl.wa-5AL.e1 / QSl.wa-5AL.e2 / QSns. wa-5AL.e1 / QSns.wa-5AL.e2 / QSns.wa-5AL.e3 / QGns.wa-5AL.e2 / QTgw.wa-5AL.e2 / QTgw.wa-5AL.e3 (672.92–700.49 Mb; Wang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 57%
“…Allelic frequency with the significance of linearity was performed using Euclidean distance (ED; Hill et al, 2013 ). ED value of each locus was calculated, the 4 th power of the original ED was set as correlation value to eliminate background noise, and Loess was used to fit the ED value ( Ji et al, 2021 ). varBScore was also used for BSE-Seq analysis ( Dong et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%